The Tiberian Pronunciation Tradition of Biblical Hebrew Volume 1 - Khan, Geoffrey (f17d769b-72bd-4974-a462-1ad0d6605dd6, 2020)
"These volumes represent the highest level of scholarship on what is arguably the most important tradition of Biblical Hebrew. Written by the leading scholar of the Tiberian Masoretic tradition, they offer a wealth of new data and revised analysis, and constitute a considerable advance on existing published scholarship. It should stand alongside Israel Yeivin's 'The Tiberian Masorah' as an essential handbook for scholars of Biblical Hebrew, and will remain an indispensable reference work for decades to come. -Dr. Benjamin Outhwaite, Director of the Taylor-Schechter Genizah Research Unit, Cambridge University Library The form of Biblical Hebrew that is presented in printed editions, with vocalization and accent signs, has its origin in medieval manuscripts of the Bible. The vocalization and accent signs are notation systems that were created in Tiberias in the early Islamic period by scholars known as the Tiberian Masoretes, but the oral tradition they represent has roots in antiquity. The grammatical textbooks and reference grammars of Biblical Hebrew in use today are heirs to centuries of tradition of grammatical works on Biblical Hebrew in Europe. The paradox is that this European tradition of Biblical Hebrew grammar did not have direct access to the way the Tiberian Masoretes were pronouncing Biblical Hebrew. In the last few decades, research of manuscript sources from the medieval Middle East has made it possible to reconstruct with considerable accuracy the pronunciation of the Tiberian Masoretes, which has come to be known as the 'Tiberian pronunciation tradition'. This book presents the current state of knowledge of the Tiberian pronunciation tradition of Biblical Hebrew and a full edition of one of the key medieval sources, Hidāyat al-Qāriʾ 'The Guide for the Reader', by ʾAbū al-Faraj Hārūn. It is hoped that the book will help to break the mould of current grammatical descriptions of Biblical Hebrew and form a bridge between modern traditions of grammar and the school of the Masoretes of Tiberias. Links and QR codes in the book allow readers to listen to an oral performance of samples of the reconstructed Tiberian pronunciation by Alex Foreman. This is the first time Biblical Hebrew has been recited with the Tiberian pronunciation for a millennium. "